Race, racism, and antiracism in emergency medicine: A scoping review of the literature and research agenda for the future. (3rd November 2022) - Darby, Anna; Cleveland Manchanda, Emily C.; Janeway, Hannah; Samra, Shamsher; Hicks, Marquita Norman; Long, Ruby; Gipson, Katrina A.; Chary, Anita N.; Adjei, Brenda A.; Khanna, Kajal; Pierce, Ava; Kaltiso, Sheri‐Ann O.; et al.
Abstract: Objectives: The objective was to conduct a scoping review of the literature and develop consensus‐derived research priorities for future research inquiry in an effort to (1) identify and summarize existing research related to race, racism, and antiracism in emergency medicine (EM) and adjacent fields and (2) set the agenda for EM research in these topic areas. Methods: A scoping review of the literature using PubMed and EMBASE databases, as well as review of citations from included articles, formed the basis for discussions with community stakeholders, who in turn helped to inform and shape the discussion and recommendations of participants in the Society for Academic Emergency Medicine (SAEM) consensus conference. Through electronic surveys and two virtual meetings held in April 2021, consensus was reached on terminology, language, and priority research questions, which were rated on importance or impact (highest, medium, lower) and feasibility or ease of answering (easiest, moderate, difficult). Results: A total of 344 articles were identified through the literature search, of which 187 met inclusion criteria; an additional 34 were identified through citation review. Findings of racial inequities in EM and related fields were grouped in 28 topic areas, from which emerged 44 key research questions. A dearth of evidence for interventions to address manifestations of racism in EM was noted throughout. Conclusions: Evidence of racism in EM emerged in nearly every facet of our literature. Key research priorities identified through consensus processes provide a roadmap for addressing and eliminating racism and other systems of oppression in EM.